Parenteral clevidipine for the acute control of blood pressure in the critically ill patient: a review - W Frank Peacock IV; Jorge E Angeles; Karina M Soto; et al (Dove Medical Press, 2009)
W Frank Peacock IV1, Jorge E Angeles2, Karina M Soto2, Philip D Lumb3,  Joseph Varon41The Cleveland Clinic, Cleveland, OH, USA; 2Universidad Autónoma de Baja California, Facultad de Medicina, Tijuana, México; 3Keck School of Medicine of University of Southern California, Los Angeles, CA, USA; 4The University of Texas Health Science Center at Houston, and The University of Texas Medical Branch at Galveston. St. Luke’s Episcopal Hospital/Texas Heart Institute, Houston, Texas, USAAbstract: Clevidipine is a new calcium channel blocker of the dihydropyridine class that is characterized by its ultra-short onset of action, vascular selectivity, small volume of distribution and extremely high clearance that coupled together result in an extremely short half-life of approximately 1 minute therefore permitting a rapid titration to the desired effect. Structurally similar to other dihydropyridines, clevidipine has an extra ester link that allows its rapid hydrolization to its inactive carboxylic acid metabolite in blood and extravascular tissues. Clevidipine’s metabolites are then primarily eliminated through urine and fecal pathways. Clevidipine does not affect cytochrome P450 (CYP) enzymes and no clinically significant drug interactions have been determined. In trials like the ESCAPE trials, ECLIPSE, and VELOCITY, clevidipine demonstrated a significant improvement in the management of acute hypertension when compared to placebo as shown in both ESCAPE trials. The ECLIPSE trial compared clevidipine to other drugs currently used in the management of acute hypertension, such as sodium nitroprusside, nitroglycerine and nicardipine; clevidipine was superior to all three agents; in providing blood pressure support, safety and tolerability clevidipine also showed a significant reduction in mortality rate (4.7% vs 1.7%, P = 0.0445) when compared to sodium nitroprusside. In the VELOCITY trial clevidipine demonstrated a reduction in blood pressure of 6% at the 3 minute mark, 15% within 9.5 minutes and 27% at the 18 hour mark.Keywords: clevidipine, calcium channel blockers, hypertensive crisis, hypertensive emergency, hypertensive urgency.